(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
It has been studied the run-out in the cutting mechanism of band saw machines. The run-out of the band saw blade is viewed as the sum of the frontal run-out of the guide wheels and the band saw blade’s own run-out. Measurements have been made on the frontal run-out of the guide wheels and on three successive full rotations of the band saw blade. It has been found that there is no repeatability of the deviations in any subsequent or preceding rotation. The main result of the study is that the frontal run-out of the guide wheels is very small compared to the actual run-out of the band saw blade, but it is the factor influencing the shape of the deviations in its rotation. It is between 0.12–0.39 mm. The total run-out of the band saw blade, in 60% of all measurements, is in the range of 0.8–1.5 mm. Various band saw blade deviations have also been identified, according to which the cutting force variation can be determined for different parts of the blade.